Unethical research trend: shadow libraries - Zeeshan, Asim; Sorooshian, Shahryar (Scielo, 2018)
Research articles spread knowledge that has been shaped by scientific communities. Access to this literature is essential for any scholar. Evidently,“biblio gifts” are easily accessible online without any charge from text-sharing platforms. Similarly, virtual groups in social networking websites such as Facebook, LinkedIn, Twitter and virtual blogs are used as pirated platforms. However little argument has been acknowledged regarding such platforms, especially concerning the size of the digital database, the major research areas covered and where these research articles come from (primary sources)